Fimasartan: A new armament to fight hypertension - Akshyaya Pradhan; Vikas Gupta; Rishi Sethi (Journal of Family Medicine and Primary Care, 2019)
Hypertension is a major public health problem of modern era. Fimasartan is a new Angiotensin Receptor Blocker approved for treatment of hypertension. It is more potent and longer acting angiotensin receptor blocker with effects lasting over 24 hours. Many clinical studies have affirmed its role in pharmacotherapy of hypertension. Further, it is renoprotective and has proven beneficial in diabetes also. This article briefly discusses the pharmacology and clinical evidence with fimasartan with a short summary of previous angiotensin receptor blockers.